2010
DOI: 10.1111/j.1399-6576.2009.02051.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal sufentanil decreases the median effective dose (ED50) of intrathecal hyperbaric ropivacaine for caesarean delivery

Abstract: Intrathecal sufentanil 5 microg produced a 28% reduction of ED50 of intrathecal hyperbaric ropivacaine for caesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 28 publications
1
47
1
Order By: Relevance
“…Unexpectedly, the present study demonstrated that the ED 50 of intrathecal bupivacaine for cesarean delivery in the Magnesium group was not reduced when compared with the Control group, suggesting that intrathecal 50 mg magnesium sulfate exhibits little or no effect on efficacy of spinal anesthesia with local anesthetics for cesarean delivery. In contrast to the lack of effect of magnesium on the median effective dose of intrathecal bupivacaine in the current study, previous studies suggested that intrathecal fentanyl or sufentanil significantly reduce the dose (ED 50 or ED 95 ) of spinal local anesthetics for cesarean delivery [3, 29, 30]. The possible underlying mechanism is that magnesium may be removed from extracellular fluid more rapidly than opioids, or that it may be specific to the NMDA receptor channel and therefore has no influence on the channels the local anesthetics act and opioid receptor sites [14, 17].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Unexpectedly, the present study demonstrated that the ED 50 of intrathecal bupivacaine for cesarean delivery in the Magnesium group was not reduced when compared with the Control group, suggesting that intrathecal 50 mg magnesium sulfate exhibits little or no effect on efficacy of spinal anesthesia with local anesthetics for cesarean delivery. In contrast to the lack of effect of magnesium on the median effective dose of intrathecal bupivacaine in the current study, previous studies suggested that intrathecal fentanyl or sufentanil significantly reduce the dose (ED 50 or ED 95 ) of spinal local anesthetics for cesarean delivery [3, 29, 30]. The possible underlying mechanism is that magnesium may be removed from extracellular fluid more rapidly than opioids, or that it may be specific to the NMDA receptor channel and therefore has no influence on the channels the local anesthetics act and opioid receptor sites [14, 17].…”
Section: Discussioncontrasting
confidence: 81%
“…The main limitations of spinal anesthesia are the relatively short duration of anesthesia and analgesia, and high incidence of hypotension. To minimize these limitations, intrathecal adjuncts such as opioids, clonidine, neostigmine and epinephrine have been reportedly used for prolonging analgesia and reducing the dose of intrathecal local anesthetic, and subsequently reducing the incidence of spinal anesthesia-induced hypotension [35]. However, intrathecal opioids such as fentanyl and sufentanil, which are commonly used as adjuncts to intrathecal local anesthetic, are associated with a number of undesirable side-effects, including delayed respiratory depression, urinary retention, and pruritus [68].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to elucidate the efficacy of intrathecal ropivacaine with adjuvants such as fentanyl (Chung et al, 2002) and sufentanil (Sun et al, 2001;Chen et al, 2010) in cesarean delivery. But intrathecal opioids will increase nausea and vomiting (Weigl et al, 2017) and itching (Sun et al, 2001;Chen et al, 2010;Sun et al, 2017) that is an uncomfortable experience and prolong the recovery for the parturients after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In China, some hospitals and centers use ropivacaine for spinal anesthesia . Ropivacaine is a type of long‐acting LA that induces a less intense and shorter‐duration motor block than bupivacaine, enabling early movement after cesarean section.…”
Section: Introductionmentioning
confidence: 99%